Pemahaman Makna Cost oleh Dosen Akuntansi - Sri Suryaningsum (The Indonesian Journal of Accounting Research, 2013)
The proper understanding of the cost meaning by accounting lecturers has been caught according to the facts empirically. This research has been focused on the variation of the meaning of cost understanding and factors that may influence them, declared in seventh (7) hypothesis that examined using ANOVA and three (3) additional analysis that examined using ANOVA on one of them, the others are in tabulation and Kruskall Wallis. ANOVA is used for independent variables that predicted able to influence the understanding of the meaning of cost, including:  the place that some one works, the university, the experience of teaching, the educational level, TOEFL, the year of graduation, the concentration of wish, and an additional declaration, that is an attention in language. The tabulation calculates respondent’s opinion with reference to the cost term, whereas Kruskall Wallis- a kind of examination that examines recognizes the resources of understanding of the meaning of cost.The respondent’s understanding of the meaning of cost is different evidently. They are 12 respondents (13.86%) haven’t recognized the meaning of cost, 62 respondents (68.13%) have been doubtful, and only 17 respondents (18.68%) that recognized the meaning of cost properly from 91 respondents. This evidence showed that there was a difference in the recognizing of the meaning of cost in accounting lecturers population.The results are: 5 hypothesis can’t be refused and 3 hypothesis have been refused successfully, included additional declaration, that is an attention in language. The hypothesis that can’t be refused is the place of work (hypothesis 1), the university (hypothesis 2), the experience of teaching (hypothesis 3), the year of graduation (hypothesis 6), the concentration of wish (hypothesis 7). The hypothesis that have been refused successfully are: the educational level (hypothesis 4), TOEFL (hypothesis 5), additional declaration, that is an attention in language.Hopefully that the workers in accounting area can use language properly. Professional organization must be careful to make standardization in the term of absorption and comparison of words in order not to be false in recognizing or understanding the meaning of that words, so the truth grammar must become an attention of IAI seriously. Analysis for the absorption and comparison of cost term indicates that there is a development of language in term of time, that there is a dynamic reality in language, so Kamus Besar Bahasa Indonesia should place cost as a word in Indonesian language.